Glial Fibrillary Acidic Protein-Expressing Glia in the Mouse Lung - Suarez-Mier, Gabriela B. (ASN Neuro, 2015)
Autonomic nerves regulate important functions in visceral organs, including the lung. The postganglionic portion of these nerves is ensheathed by glial cells known as non-myelinating Schwann cells. In the brain, glia play important functional roles in neurotransmission, neuroinflammation, and maintenance of the blood brain barrier. Similarly, enteric glia are now known to have analogous roles in gastrointestinal neurotransmission, inflammatory response, and barrier formation. In contrast to this, very little is known about the function of glia in other visceral organs. Like the gut, the lung forms a barrier between airborne pathogens and the bloodstream, and autonomic lung innervation is known to affect pulmonary inflammation and lung function. Lung glia are described as non-myelinating Schwann cells but their function is not known, and indeed no transgenic tools have been validated to study them in vivo. The primary goal of this research was, therefore, to investigate the relationship between non-myelinating Schwann cells and pulmonary nerves in the airways and vasculature and to validate existing transgenic mouse tools that would be useful for studying their function. We focused on the glial fibrillary acidic protein promoter, which is a cognate marker of astrocytes that is expressed by enteric glia and non-myelinating Schwann cells. We describe the morphology of non-myelinating Schwann cells in the lung and verify that they express glial fibrillary acidic protein and S100, a classic glial marker. Furthermore, we characterize the relationship of non-myelinating Schwann cells to pulmonary nerves. Finally, we report tools for studying their function, including a commercially available transgenic mouse line.